2008
DOI: 10.1093/toxsci/kfn104
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Urinary Beta-Defensin-1 Expression as a Biomarker of Response to Arsenic

Abstract: Ingestion of arsenic (As) through contaminated drinking water results in increased risks of skin, lung, kidney, and bladder cancers. Due to its association with kidney and bladder cancers, we hypothesized that analysis of the urinary proteome could provide insight into the mechanisms of As toxicity. Urine from participants in a cross-sectional As biomarker study conducted in Nevada, classified as having either high (>or= 100 microg total urinary As/l) or low exposure (< 100 microg total urinary As/l) was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Examination of the urinary proteome in a human population exposed to As revealed decreased expression of human β-defensin-1 (HBD-1) peptides in the urine of men with high As exposure from Nevada (Hegedus et al, 2008). We replicated these findings in a second, independent As exposed population from Chile, and validated the relationship between As exposure and HBD-1 in vitro.…”
Section: Proteomic Biomarkers Of Arsenic Exposuresupporting
confidence: 52%
See 1 more Smart Citation
“…Examination of the urinary proteome in a human population exposed to As revealed decreased expression of human β-defensin-1 (HBD-1) peptides in the urine of men with high As exposure from Nevada (Hegedus et al, 2008). We replicated these findings in a second, independent As exposed population from Chile, and validated the relationship between As exposure and HBD-1 in vitro.…”
Section: Proteomic Biomarkers Of Arsenic Exposuresupporting
confidence: 52%
“…As with transcriptomics, proteomic studies of human-exposed populations are currently limited and include studies by our group and others of populations exposed to benzene and arsenic (Zhai et al, 2005;Harezlak et al, 2008;Hegedus et al, 2008). Advances are continuing to be made in the discovery of protein biomarkers of disease (Hanash et al, 2008;Howes et al, 2008), which together with exposure-related proteomic profiles will facilitate an understanding of disease mechanisms.…”
Section: Proteomicsmentioning
confidence: 99%
“…In addition, two recent studies demonstrated the significant potentials of mass spectrometry proteomics to identify the arsenic biomarkers of effect. Hegedus et al (2008) conducted urine proteomic analyses and observed that in highly arsenic exposed men (well water >500 µg arsenic/L), there was an increased level of human β-defensin-1 (HBD-1). Harezlak et al (2008) showed significant associations of arsenic exposure to either under-or over-expression of 20 proteins in the plasma of highly arsenic exposed study participants selected from a large arsenic case control study of skin disease in Bangladesh.…”
Section: Biomarkers Of Effectmentioning
confidence: 99%
“…Previous studies have analyzed arsenic-exposed human serum and urinary proteomic profiles and identified several potential biomarkers (Harezlak et al, 2008;Hegedus et al, 2008;Zhai et al, 2005). According to the IARC, skin shows the strongest association between chronic arsenic exposure and cancer (IARC, 2004), and dermal manifestations such as hyperpigmentation and hyperkeratosis are diagnostic of chronic arsenicosis.…”
Section: Introductionmentioning
confidence: 99%